GROUP DECISION SUPPORT SYSTEM (GDSS) UNTUK MENENTUKAN PRIORITAS PROYEK - Nur Heri Cahyana (Telematika, 2014)
Every year Yogja Infoservice Company get many offers information technology projects. Priority projects need to be done for efficiency and effectiveness of work with the joint meetingmechanism by a number of employees in charge of three things: technical, financial andadministrative Each field considered priority projects according to criteria that belong to each ofthese fields , which of profitable projects to take precedence in a more objective and prioritizedby each business unit in the company. Because of the decision reached by the collaborativework of three units of Decision Support Systems must be built Group Decision Support System (GDSS ) . Methods of decision-making for each group using the Weighted Product ( WP ) andthe decisions of each group collaborated with BORDA method . The research methodologyuses a System Development Life Cycle and systems development approach using structuredmethods . Results of the study was a model project selection decision support applications thatimplement both methods . The results have been tested and can be used in the system .Keyword : Group Decision Support System, BORDA, Priority projects